Role of Kanchanara Twaka Kwatha with Shunthi Churna in Hypothyroidism (Dhatuwagni Vikriti) (International Journal of Ayurveda and Pharma Research, 2023)
The thyroid is an important part of human endocrine system which are responsible for regulation of oxygen use, BMR, cellular metabolism and growth and development. Hypofunctioning of Jatharagni which in turn effect Dhatwagni eventually brings out Pathological sequence and ultimately the disease condition develop. In hypothyroidsim etiological factors mainly vitiate Tridosha (Kapha predominance along with Pitta vitiation and Margavarana leading to provoking of Vata). The line of treatment with specific target to Rasavaha, Mamsavaha, Medovaha, Manovaha Srotas as well as Vata-Kapha Nashaka, Agnideepan, Sroto Shodhana, Vatanuloman, Amapachan treatment should be administered in hypothyroidism. Keeping the same in mind, present study was carried out to assess the role of Kanchanara Twaka Kwatha with Shunthi Churna in hypothyroidism (Dhatuwagni Vikriti). For this study 40 patients were selected and are divided into two groups with 20 patients in each group on the basis of inclusion and exclusion criteria and were assessed on the basis of subjective and objective parameters by applying appropriate statistical test. Most of the patients in group 1 (Kanchanaradi Kwatha) shows marked improvement in their symptoms as well as in objective parameters (thyroid profile) as compared to group 2 (Tab. Levothyroxine 50 mcg) which was taken as control group. From this study it can be concluded that hypothyroidism can be managed effectively with Kanchanara Twaka Kwatha with Shunthi Churna mention in Sharangdhar Samhita Madhyam Khanda Adhyaya 2 Shloka no.126.